Plasma Functionalized Scaffolds of Polyhydroxybutyrate Electrospun Fibers for Pancreatic Beta Cell Cultures - Cortés-Ortiz, Emma; Olayo-Valles, R.; Rodríguez-Talavera, Rogelio; González-Torres, Maykel; Vargas-Muñoz, Susana; Olayo, R.; Godinez-Fernández, R.; Uribe Juárez, Omar Eduardo; Morales-Corona, Juan (Frontiers in Materials, 2021)
Polyhydroxybutyrate (PHB) scaffolds, produced by electrospinning and coated by plasma polymerization of pyrrole, were used as cell culture substrate for beta cells. PHB is a natural polymer that is biocompatible and bioresorbable. The electrospinning conditions used, produced scaffolds with large surface area and high porosity. The scaffold surface was modified by plasma polymerization of pyrrole doped with iodine (PPyI). The morphology of the scaffolds was characterized by scanning electron microscopy, while FTIR and Raman spectroscopy were used to characterize the composition. Crystallinity of the PHB fibers was characterized by X-ray diffraction and differential scanning calorimetry. Pancreatic beta cells (from the RIN-M cell line) were cultured on PHB and PHB-PPyI scaffolds. Cell viability results showed that the surface modified material is a good cell culture substrate for beta cells.